PENGEMBANGAN BAHAN AJAR KIMIA MENGGUNAKAN SOFTWARE ADOBE FLASH CS6 PADA MATERI SISTEM KOLOID - Julita Sastra; Sura Menda Ginting; Febrian Solikhin (University of Bengkulu, 2023)
This research was the development of chemistry teaching materials using Adobe Flash CS6 software which aimed to determine the feasibility level, readability level, and student response to chemistry teaching materials on the subject of colloid system. The development of this teaching materials used the ADDIE development model which was limited to the implementation stage. The research was conducted at MAN 1 Bengkulu City with the research subjects being 9 students of class XI IPA 2 for the teaching materials readability test and all students of class XI IPA 2 totaling 33 students for testing student responses to the teaching materials. From the results of the study, it was found that (1) the feasibility level of this teaching materials was 88.33% meanwhile the result from the media aspect was 87% therefore based on the validation results by the validator of the teaching materials developed using Adobe Flash CS6 software it was declared very valid, (2) based on the results of the teaching materials readability trial, the average percentage of teaching materials readability obtained was 84.04% with a very valid category, (3) based on the product trial, the average student response was 89.67% with a very valid category. Keywords: Teaching Materials, Adobe Flash CS6, Coloid System